2021
DOI: 10.1073/pnas.2101826118
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between birth timing, circuit wiring, and physiological response properties of cerebellar granule cells

Abstract: Cerebellar granule cells (GrCs) are usually regarded as a uniform cell type that collectively expands the coding space of the cerebellum by integrating diverse combinations of mossy fiber inputs. Accordingly, stable molecularly or physiologically defined GrC subtypes within a single cerebellar region have not been reported. The only known cellular property that distinguishes otherwise homogeneous GrCs is the correspondence between GrC birth timing and the depth of the molecular layer to which their axons proje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…The circuit, which could account for the previously observed short-latency cerebello-amygdala responses (Heath and Harper, 1974), could convey cerebellar information about prediction, salience, and/or valence to BLA, shaped by the intrinsic, synaptic, and integrative properties of the nodes. Indeed, the cerebellum is known to encode such information (Ohmae and Medina, 2015;Wagner et al, 2017;Hull, 2020;Ma et al, 2020;Bina et al, 2021;Shuster et al, 2021), which is also seen in BLA (Paton et al, 2006;Adolphs, 2010;Janak and Tye, 2015;Sengupta et al, 2018;Zhang and Li, 2018;Gründemann et al, 2019;Brockett et al, 2021), and which is thought to be used by CM and PF during aversive conditioning, observational learning and reward-seeking behavior (Jeon et al, 2010;Sengupta and McNally, 2014;Vertes et al, 2015;Xiao et al, 2018;Cover and Mathur, 2021;Rizzi et al, 2021).…”
Section: Proposed Functions Of the Dcn-bla Circuitmentioning
confidence: 99%
“…The circuit, which could account for the previously observed short-latency cerebello-amygdala responses (Heath and Harper, 1974), could convey cerebellar information about prediction, salience, and/or valence to BLA, shaped by the intrinsic, synaptic, and integrative properties of the nodes. Indeed, the cerebellum is known to encode such information (Ohmae and Medina, 2015;Wagner et al, 2017;Hull, 2020;Ma et al, 2020;Bina et al, 2021;Shuster et al, 2021), which is also seen in BLA (Paton et al, 2006;Adolphs, 2010;Janak and Tye, 2015;Sengupta et al, 2018;Zhang and Li, 2018;Gründemann et al, 2019;Brockett et al, 2021), and which is thought to be used by CM and PF during aversive conditioning, observational learning and reward-seeking behavior (Jeon et al, 2010;Sengupta and McNally, 2014;Vertes et al, 2015;Xiao et al, 2018;Cover and Mathur, 2021;Rizzi et al, 2021).…”
Section: Proposed Functions Of the Dcn-bla Circuitmentioning
confidence: 99%
“…Intriguingly, several recent studies have shown that the cerebellum contains reward related information 88,[96][97][98][99][100][101][102][103] . In addition to the recently described direct projection of cerebellum to one of the major reward processing brain regions, the ventral tegmental area 104 , the Cb-SNc pathway described here may also serve as a medium through which information about reward and other non-motor behaviors might be conveyed from the cerebellum to the basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…The circuit, which could account for the previously observed short-latency cerebello-amygdala responses 37 , could convey cerebellar information about prediction, salience and/or valence to BLA, shaped by the intrinsic, synaptic and integrative properties of the nodes. Indeed, the cerebellum is known to encode such information 8,[69][70][71][72][73] , which is also seen in BLA 35,[74][75][76][77][78][79] , and which is thought to be used by CM and PF during aversive conditioning, observational learning and reward-seeking behavior 30,46,[80][81][82][83] .…”
Section: Proposed Functions Of the Dcn-bla Circuitmentioning
confidence: 99%